Implementation of native tree species in Rwandan forest plantations - Stelstra, Roberto Enrico (2021)
The forest plantations in Rwanda have been dominated by monocultures of exotic species, primarily Eucalyptus and Pinus, for the last 100 years. This type of monoculture leaves the forests vulnerable to disturbances like pests and droughts, and has a negative impact on the species biodiversity in the Rwandan forests. In 2018, the Rwandan Forest Authority released a revised version of their National Forest Policy, in which they recognize the importance of practising a more sustainable form of forestry. Through interviews and literature research this study has aimed to find out which products and traits are sought after in the Rwandese forestry sector, which native species possess these traits and if they could be a competitive alternative to the current exotic species. I found that timber production still is the main priority in the Rwandan forestry sector, but ecological value, services for local communities and medicinal qualities are also valued. The qualities and traits of eleven potentially useful, native tree species have been analysed and compared. A selection of potentially useful species was made based on their biophysical requirements, their wood quality and the non-timber forest services they could provide. Of these species Maesopsis eminii, Markhamia luta, Prunus Africana and Milicia excelsa seem promising alternatives to the established exotic plantation species. Based on those four species a management plan for a mixed-species plantation has been designed, which will be implemented and monitored by the Rwandese forest company SEAL Ltd.